(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Resolution of the Government of the Republic of Kazakhstan dated August 23, 2012 approved a new model of Standard curriculum on the subject «The Russian language» for grades 5–9 of secondary education (with Russian as the language of education). Therefore, the textbooks for the Kazakh secondary schools had to be revised, modified and supplemented to meet the new standard. This paper reviews the innovations introduced by the authors into the main Russian textbook for the 7th grade and into the alternative textbook for 8th grade of the secondary school.